Genuskongruens och genus i finska gymnasisters inlärarsvenska - Lahtinen, Sinikka (1998)
The present study explores how Finnish learners use uter and neuter forms in their Swedish interlanguage and what kinds of errors they make in using the forms. The data consisted of essays written by 342 pupils in the 1st and 3rd grades of the Finnish upper secondary school. A test was designed to investigate further some phenomena, infrequent in the essays, and to separate procedural from declarative knowledge. The analysis of the 6,654 gender markings in the essays showed that the use of uter gender markers was easier for the the Finnish learners than the use of the neuter ones. Uter forms dominate in the target language and also in the analysed textbooks. The mastery of the different markers varied: gender marking of definite suffixes was almost error-free, whereas the marking of adjectives and definite articles caused difficulties. The latter categories occurred rarely in the essays compared with the definite suffix. Rote learning and learning of the noun and the suffix as an unanalyzed whole may partly explain the high degree of correctness shown by the pupils in handling the definite suffix in free written production. Compared to the second language learners in Andersson's study (1992), the Finnish foreign language learners showed a significantly higher accuracy in the use of neuter gender markers. It is thus suggested that foreign language learners may benefit from focusing their attention on gender marking done in teaching, whereas informal learners may not pay sufficient attention to neuter gender markers which occur less often in input, their proportion being approximately 20-30 %. 379 pupils in 10 different upper secondary schools were tested and it was shown that adjective attributes which can take different forms depending on the preceding determiner constitute the main problem for the learners. When the gender of the noun was given, but the noun was unfamiliar to the learners, accuracy rates in the choice of the gender form of determiners were not as high as expected. It appears that some suffixes facilitated gender assignment, and the pupils seemed to understand that these suffixes determine the gender of the noun. The most difficult part of the test, however, was the one where pupils were expected to identify and correct wrong gender forms in a text. As a whole, the learners were rather inconsistent in assigning gender in the test.